Lipinia vittigera (Sipora Striped Skink) - Muhammad Aini, Ujang; Hadimar, .; Sánchez, K.L.; Maiwald, M.J.; Das, Indraneil (Society for the Study of Amphibians and Reptiles, 2021)
A new record of the scincid lizard, Lipinia vittigera from Kalimantan Barat is presented.